Using multi-terminology indexing for the assignment of MeSH descriptors to health resources in a French online catalogue - Pereira, Suzanne (American Medical Informatics Association, 2008)
BACKGROUND: To assist with the development of a French online quality-controlled health gateway (CISMeF), an automatic indexing tool assigning MeSH descriptors to medical text in French was created. The French Multi-Terminology Indexer (F-MTI) relies on a multi-terminology approach involving four prominent medical terminologies and the mappings between them. OBJECTIVE: In this paper, we compare lemmatization and stemming as methods to process French medical text for indexing. We also evaluate the multi-terminology approach implemented in F-MTI. METHODS: The indexing strategies were assessed on a corpus of 18,814 resources indexed manually. RESULTS: There is little difference in the indexing performance when lemmatization or stemming is used. However, the multi-terminology approach outperforms indexing relying on a single terminology in terms of recall. CONCLUSION: F-MTI will soon be used in the CISMeF production environment and in a Health MultiTerminology Server in French.